Masnavi (Couplet) - As the Basis of Event Poetry - Rakhmonova Shahnoza Muhitdinovna (Genius Journals, 2022)
This article describes the metric characteristics of Habibi, Sabir Abdulla, Chusti in Uzbek poetry of the second half of the XX century, the possibilities of measurement, the system of rhyme, the harmony of content, and reveals the scientific significance of the genre. The role of the Masnavi (couplet) genre in the poetry of the period is also analyzed.
Keywords: Aruz; genre; metric; masnavi